SYSTEMATIC LITERATURE REVIEW : PEMANFAATAN BIG DATA DALAM PENGAMBILAN KEPUTUSAN SEKTORAL DI INDONESIA - Mustika, Rony; Veri, Jonh (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the utilization of Big Data in sectoral decision-making in Indonesia through a Systematic Literature Review (SLR) approach. The review is based on 200 scientific articles from various databases, refined using the PRISMA protocol, resulting in 7 eligible studies. The analysis reveals that Big Data has been applied in multiple sectors including health, public policy, logistics, smart cities, information systems, corporations, and organizations. The findings highlight that Big Data plays a vital role in supporting evidence-based decision-making, enhancing operational efficiency, and strengthening strategic and competitive capabilities. The study also identifies gaps in the literature, especially in less-explored sectors such as education and agriculture. Hence, Big Data is positioned not only as an information source but also as a strategic instrument in Indonesia’s sectoral digital transformation. Keywords: Big Data, decision making, public sector, systematic literature review, Indonesia